Health system in Peru - Alcalde-Rabanal, Jacqueline (2019)
In this document, updated information of the Health System of Peru is presented in order to understand its structure, the main changes and the results in health. An agile format has been used so that it can be used by decision makers, the academic community and others interested in Peru's Health system. In the first part, information on the demographic and social context of the country is presented; as well as the health conditions of the Peruvian population to which the health system has to respond. In the second part, the characteristics of the health system related to its structure and coverage, the sources of financing, the resources available to assist the population (humans, health facilities and medicines) are described; the rectory of the system; and the mechanisms for the exercise of health citizenship. Finally, the challenges that Peru's health system must assume to achieve effective universal coverage for all Peruvians are described.